Menemukan Tren Baru di Kalangan Pemuda: Analisis Pola Praktik Perjudian Toto Gelap di Kabupaten Klaten - Fatahillah, Abdul; Hakim, Ummu Habibah (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
From the perspective of religion, positive law, and noble values that develop in society, Toto Gelap (togel) gambling is considered a negative behavior. However, in reality, gambling is still favored by the community, including the youth of the Klaten Selatan sub-district, who are supposed to be agents of change. This study aimed to analyze the practice of dark toto gambling from the perspective of Islamic Law Sociology. This research includes qualitative research using a sociological approach in which the Theory of Social Behavior is used as an analytical knife. Data were collected through observation, interviews, and documentation.  The results showed that the existence of togel gambling can be described in several practice patterns, including gambling patterns for profit, gambling patterns for entertainment, gambling patterns to try luck, and gambling patterns due to easy access to play. The playing factors are the benefit factors and players’ perceptions of gambling. Gambling on a togel is included in the category of operant behavior, where gambling behavior can be formed and learned from a learning process, and is prone to be repeated because there are benefits of gambling on the togel.